Detection of distant metastasis and prognostic prediction of recurrent salivary gland carcinomas using 18F‐FDG PET/CT. (8th June 2018) - Lee, Sang Hun; Roh, Jong‐Lyel; Kim, Jae Seung; Lee, Jeong Hyun; Choi, Seung‐Ho; Nam, Soon Yuhl; Kim, Sang Yoon
Abstract: Objective: To compare the diagnostic accuracy of 18 F‐FDG PET/CT and conventional contrast‐enhanced CT for the re‐staging of recurrent salivary gland carcinoma (SGC). Materials and Methods: This study included 58 consecutive patients who underwent recurrent SGCs after definitive treatment. The recurrences were evaluated by 18 F‐FDG PET/CT and contrast‐enhanced CT of the neck and chest. McNemar's test was used to compare the diagnostic accuracy of 18 F‐FDG PET/CT with standard neck and chest CT imaging, and a Cox proportional hazards model was used to assess the prognostic value of PET/CT. Results: Of 58 patients with recurrent SGCs, 17 (29%) had a local recurrence, 17 (29%) had a regional recurrence, and 38 (66%) had a distant metastasis, with these classifications showing overlap. The sensitivity and accuracy of 18 F‐FDG PET/CT for the detection of distant metastases were significantly higher than those of CT ( p < 0.05), whereas, for detection of loco‐regional recurrences, they did not differ ( p > 0.1). The 18 F‐FDG PET/CT‐positive findings at distant sites were predictors of poor progression‐free and overall survival outcome (all p < 0.05). Conclusions: 18 F‐FDG PET/CT is a more effective method than CT for detecting distant site recurrences of SGC. This may lead to prognostic prediction for recurrent SGCs.